1992
DOI: 10.3354/meps081205
|View full text |Cite
|
Sign up to set email alerts
|

Depth-size trends in western Mediterranean demersal deep-sea fishes

Abstract: We analyze the bathymetric trends of demersal deep-sea flshes in the Catalan Sea ( N W Medlterranean) between 1000 and 2250 m depth In the first part of the study, only the pattern shown by the whole fauna ( wthin-fauna pattern ) 1s considered At 1200 m there is a significant decrease In fish mean welght, as a consequence of the replacement of the dominant large or medium-sized specles by small ones This fauna1 shift may be a consequence of the lower trophic availability at greater depths, as shown by an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 21 publications
6
91
2
2
Order By: Relevance
“…Thus, in areas with large densities, the smaller crabs clearly occupied shallower depths and larger individuals were concentrated in deeper areas. There is data in the literature on size relationships as a function of depth in many taxa, with patterns often difficult to generalise (Stefanescu et al 1992, Carbonell et al 2003. Previous studies on the distribution characteristics of L. depurator have also detected strong geographic variability in densities (Abelló 1986(Abelló , 1993, as well as the key role of depth in structuring populations in regard to both density and size structure (Mori & Zunino 1987, Abelló et al 1988, Abelló 1993, with a tendency for small sizes to be found in shallower waters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in areas with large densities, the smaller crabs clearly occupied shallower depths and larger individuals were concentrated in deeper areas. There is data in the literature on size relationships as a function of depth in many taxa, with patterns often difficult to generalise (Stefanescu et al 1992, Carbonell et al 2003. Previous studies on the distribution characteristics of L. depurator have also detected strong geographic variability in densities (Abelló 1986(Abelló , 1993, as well as the key role of depth in structuring populations in regard to both density and size structure (Mori & Zunino 1987, Abelló et al 1988, Abelló 1993, with a tendency for small sizes to be found in shallower waters.…”
Section: Discussionmentioning
confidence: 99%
“…After logarithmic transformation (MidBiological sampling. During the 9 seasonal surdleton & Musick 1986, Stefanescu et al 1992), means veys, either all specimens or a random subsample of of abundance (ind. n mile-') and biomass (g n mile-2) at least 100 individuals from each haul were meawere calculated for each cruise (1) for each 50 m botsured and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…More detailed studies on the causes of the ontogenetic movements have concentrated on long-lived species, especially cod and plaice (Harden Jones 1968), but similar investigations are lacking for short-lived species like red mullet. Stefanescu et al (1992) noted that further study of this subject should center on the autoecology of each species, as the complexity of links established by a species with its environment will result in highly variable and specific adaptive responses in each case.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the demersal deep-sea ichthyofauna indicated a general pattern of increased size with depth (Polloni et al 1979), which came to be known as Heincke's Law (following Heincke's (1913) description of the size of plaice in the North Sea). However, subsequent work demonstrated that the phenomenon was not ubiquitous (Snelgrove & Haedrich 1985), may be an artefact of sampling (Merrett et al 1991b) and in some regions a decline in size with depth has been reported (Stefanescu et al 1992).…”
Section: Introductionmentioning
confidence: 99%